2022
DOI: 10.1136/bmjopen-2022-060805
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden caused by respiratory syncytial virus compared with influenza among adults: a retrospective cohort study from Eastern Finland in 2017–2018

Abstract: ObjectivesRespiratory syncytial virus (RSV) is one of the most important causes of lower respiratory tract illnesses. In this study, we examined the number and severity of RSV infections among adult patients. The underlying diseases and background information of patients with RSV were examined and compared with the patients with influenza.DesignRetrospective cohort study.SettingPatients receiving tertiary care services in Kuopio University Hospital (KUH) district in Eastern Finland.Participants725 patients (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…Broadening of Egypt ARI surveillance laboratory testing panel to include RSV and other respiratory viruses is recommended to better characterize the relative burden of ARI in Egypt. During RSV and influenza epidemics, it is particularly important to test for influenza and RSV to better identify the causative virus and prevent infection from spreading to elderly and chronically ill individuals [ 43 – 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broadening of Egypt ARI surveillance laboratory testing panel to include RSV and other respiratory viruses is recommended to better characterize the relative burden of ARI in Egypt. During RSV and influenza epidemics, it is particularly important to test for influenza and RSV to better identify the causative virus and prevent infection from spreading to elderly and chronically ill individuals [ 43 – 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last four years, several systematic reviews and meta-analyses were published [ 15 , 16 , 17 , 25 , 27 , 29 , 31 , 32 , 41 ], most of them with the aim to define the disease burden of RSV in older adults and some of them with the active participation of pharma companies involved in RSV vaccine and drug development. Several clinical studies have been published over the years worldwide [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. In Europe, what emerged together with the findings of few multicenter clinical studies [ 21 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] was the need to harmonize and collaborate between the various laboratories in order to obtain shared diagnostic protocols with which to compare data...…”
Section: Can We Consider Rsv a Forgotten Pathogen In Older Adults?mentioning
confidence: 99%
“…A systematic review and meta-analysis has shown that RSV and influenza virus infection of older adults leads to a similar rate of hospitalization and mortality [25]. In contrast, a retrospective cohort study from Eastern Finland in 2017–2018 showed that RSV-infected patients were older and had an increased risk of hospitalization and mortality in comparison to influenza virus-infected adults [26 ▪▪ ]. The level of RSV infection in adults and older adults may also be underestimated due to limitations in diagnostic testing, a situation that could be alleviated by the collection and testing of three or more specimen types from patients [27].…”
Section: Vaccinesmentioning
confidence: 99%